2011
DOI: 10.1007/s10554-010-9780-3
|View full text |Cite
|
Sign up to set email alerts
|

MDCT differentiation between bicuspid and tricuspid aortic valves in patients with aortic valvular disease: correlation with surgical findings

Abstract: To identify multi-detector computed tomographic (MDCT) features discriminating bicuspid aortic valves (BAVs) from tricuspid aortic valves (TAVs) in patients with aortic valvular disease using surgical findings as reference. Forty-five patients underwent ECG-gated cardiac MDCT scans prior to aortic valve replacement. Morphologic patterns of aortic valves on MDCT were classified into: bicuspid without raphe (A), fused valve with a fish-mouth opening (B), fused valve without a fish-mouth opening (C), and tricuspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It would also be difficult to perform unbiased individual interpretations during surgery. However, intra‐operative scoring has been successfully used as the reference in other studies aimed at evaluating accuracy in diagnosing AVC and BAV (Roberts et al ., ; Alkadhi et al ., ; Joo et al ., ). One may argue that surgeons do not focus on the details of the structure of valves explanted during surgery and that the valve details are usually not included in the routine report, or the report is not written in direct relation to surgery.…”
Section: Discussionmentioning
confidence: 97%
“…It would also be difficult to perform unbiased individual interpretations during surgery. However, intra‐operative scoring has been successfully used as the reference in other studies aimed at evaluating accuracy in diagnosing AVC and BAV (Roberts et al ., ; Alkadhi et al ., ; Joo et al ., ). One may argue that surgeons do not focus on the details of the structure of valves explanted during surgery and that the valve details are usually not included in the routine report, or the report is not written in direct relation to surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Cells were mixed with triosite (Zimmer) and were incubated for 1 h. Transplanted cells then were mixed with fibrinogen and thrombin before being implanted into a subcutaneous pocket of an 8-wk-old C57 mouse. Eight weeks later, ectopic mineralization was assessed by X-ray (TU-3000DR, Hitachi) and CT (Somatom Definition; Siemens Medical Solutions, Forchheim, Germany) and was quantified using the Agatston score [32],[55],[56]. Ectopically mineralized tissues were harvested and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a calcified bicuspid aortic valve with a raphe was confirmed at the time of surgery and asymmetric, leading to an asymmetrically limited motion and reduced opening of the valves. In some cases, valvular calcification extends from one cusp to the next and results in cusp fusion without a fish mouth opening (a similar appearance to that seen in patients with BAV) [1,27,28]. In patients with rheumatic AS, two or more of the three commissures are often fused, and the cusps may be either diffusely or focally fibrotic with or without commissural fusion or calcification [1,28].…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, differentiation between BAV and TAV with CCTA and CMR was difficult due to fused cusps without a fish mouth opening, which resulted in misclassification of 9 AV and 7 AV, respectively. Joo et al [27] recently reported that the CCTA features of uneven cusp sizes, round-shaped openings, midline calcifications at the cusp fusion, and longer cusp fusions were strongly associated with BAV in patients with a fused valve with a fish mouth opening and a fused valve without a fish mouth opening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation